EVALUATING THE EFFECTIVENESS OF DIFFERENT ORAL HYGIENE INTERVENTIONS IN PREVENTING PERI-IMPLANTITIS - Feras waleed shaikh; Waleed Abdulrahim Aljehani; Abdulkader Abdulelah Abulhamayel; ‏ Omar Muhammed Abunawas; Anmar Essam Kattan; Abdullah Sameer Kaki; Roaa Mohammad AlDomyati; Rozan Sameer A Nasruddin; Hussam Kamalualddin M Almadani; Wael Hisham Rajkhan; Mazen Ahmad Almarshadi; jamal Adel salla; et al. (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Peri-implantitis is a common inflammatory condition that affects the soft and hard tissues surrounding dental implants. It poses a significant challenge in implant dentistry due to its potential to cause implant failure. Various oral hygiene interventions have been proposed to prevent peri-implantitis, but their effectiveness remains a topic of debate. This review article aims to critically evaluate the efficacy of different oral hygiene interventions in preventing peri-implantitis. The review will analyze existing literature on interventions such as mechanical plaque removal techniques, chemical agents, antimicrobial mouth rinses, and adjunctive therapies like photodynamic therapy and laser treatments. The effectiveness of these interventions in reducing plaque accumulation, controlling inflammation, and preventing peri-implant bone loss will be assessed. Furthermore, the review will explore the impact of patient-related factors, such as compliance with oral hygiene instructions and systemic health conditions, on the success of these interventions.Key themes that will be discussed include the role of biofilm management in peri-implant health, the importance of personalized oral hygiene regimens, and the potential of novel technologies in improving implant maintenance outcomes. By synthesizing current evidence, this review aims to provide insights into the most effective strategies for preventing peri-implantitis and promoting long-term implant success.